Relative importance of hazards at construction sites - Jabbarani Torghabeh, Zahra (2013)
Construction hazard identification is one of the fundamental steps in construction safety management therefore identifying hazards and determining their severities of consequences are extremely important. The aim of this study is to investigate and rank the construction hazards in order of the severity of consequences. The data for this study were collected using a questionnaire survey, distributed among respondents randomly selected from construction sites within Malaysia. The results of this study indicated that the most critical construction hazards are Awkward postures, Forceful exertions and Physical injury hazards which originate from process of work and manual handling of operations and equipments. On the contrary Blue green algae and Fungi are the least critical construction hazards which are not critical threats to the safety and health of construction workers. In addition to training and educational purposes, the results of this study can be used in preparing appropriate construction safety and health plans.